Influence of implanting grazing steers with Ralgro® or Synovex-S® followed by Synovex® Plus™ or a Ralgro®/Synovex® Plus™ reimplant program in the feedlot on pasture/finishing performance and carcass merit - Fankhauser, T.R.; Kuhl, Gerry L.; Simms, D.D.; Stokka, Gerald L.; Drouillard, James S.; Blasi, Dale A. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
In an 84-day pasture/132-day finishing study using 480 crossbred steers (675 lb), Ralgro® increased (P<.05) pasture gains 9.3% compared to nonimplanted controls. Gains of Synovex-S®-implanted steers were intermediate. Pasture treatments were split into two finishing-phase implant treatments: Synovex® Plus™ or initial Ralgro with a Synovex Plus reimplant on day 56. No interactions occurred between pasture and finishing implants with respect to finishing performance or carcass traits. Steers on the Synovex Plus treatment gained 11.7% faster and 7.9% more efficiently (P<.01) during the first 56 days of the finishing phase than the Ralgro-implanted steers. However , when those steers were reimplanted with Synovex Plus, they gained 22.2% faster and 21.1% more efficiently (P<.01) during the last 76 days. Over the entire 132-day finishing phase, the feedlot reimplant program improved rate (4.0%; P<.06) and efficiency (7.5%; P<.01) of gain compared to Synovex Plus alone. Overall , gains and intakes during the finishing phase were similar for all pasture implant treatments. However, control pasture steers were 4.5% more efficient (P<.08) than Ralgro and Synovex steers during the finishing phase. Neither pasture or finishing implant treatment influenced carcass traits. This study indicates that implanting during grazing may reduce feed efficiency during the finishing phase, especially when a feedlot reimplant program is not used. However, this finding disagrees with several previous research studies where pasture implantation had no effect on feedlot performance.
Keywords: Beef; Ralgro; Synovex; Synovex Plus; Pasture; Finishing; Carcass; Implants